Pelatihan Kiat Belajar Membaca Alquran Dengan Mudah Dan Menyenangkan Bagi Lansia Dengan Metode Ummi - Yuniarsih Sawaliyah; Azhar; Murah; Hayun Aini (Universitas Merdeka Surabaya, 2026)
This community service activity aims to improve the reading ability of the Qur’an for the elderly through the simple and gradual Ummi method. providing spiritual guidance so that the elderly feel calmer, happier, and more enthusiastic in worship; creating an inclusive learning environment at LKSLU, so that the elderly feel valued and remain productive by fostering a lifelong learning spirit among senior citizens; foster social concern among the surrounding community for the spiritual needs of the elderly; and strengthen religious values and a sense of togetherness among students, LKSLU administrators, the elderly, and the surrounding community. The implementation method of this service includes counseling, practice, and individual mentoring. The evaluation instruments used were the Participant Attendance List, Qur'an Reading Test, Participant Satisfaction Questionnaire, Facilitator Observation, and Activity Documentation, which were analyzed descriptively. The results of this service show an increase in the knowledge and understanding of the elderly about the methods of learning the Quran, making it easy; an improvement in the students' skills in reading the Quran. This can be seen from the fact that most participants are able to improve their ability to correctly read the Arabic letters; participants who previously only knew the basic letters can now read short surahs; the elderly feel more enthusiastic about participating in religious activities at LKSLU Al Athar; a good emotional relationship is established between students, administrators, and participants.